(untitled) (Research, Society and Development, 2022)
The Amazon basin is impressive, with rivers, streams and creeks of different sizes, supplied by flowing springs, protected by Permanent Preservation Areas - PPA, enabling the existence of this aquifer network. For many, the areas are not important, especially for landowners who see them as lost places, where nothing is produced. Even with legislation, part of these areas are used for extensive pasture, causing soil compaction, erosion and harm to the water body. Seeking to understand the impacts suffered by the Jaçanã Azul stream, Juína/MT, two methods were applied: Diagnosis of Springs - which allows understanding the situation of the springs; VERAH method - which makes it possible to analyze the situation of the micro-basin. The three springs were classified as degraded, little and very disturbed, as a result of the removal of native vegetation and the implementation of extensive pastures. The micro-basin is not preserved, but it does not suffer high anthropic pressure, after all, although close to the urban area, it is located in a rural area, running its entire length among farms, which make use of this stream for various purposes. The need for environmental awareness actions and intervention regarding the recovery of riparian forest is notorious, both at the sources and in the body of the stream, as these actions result in a better, more balanced environment with abundant water.